Effectiveness of Foot Reflexology to Reduce Anxiety in A Patient with Coronary Artery Disease after Cabg: A Case Study - Nur Asnah Sitohang; Evelina Naibaho (GLOBAL HEALTH SCIENCE GROUP, 2025)
Coronary Artery Disease (CAD) remains a leading cause of mortality worldwide and often requires Coronary Artery Bypass Graft (CABG) surgery. Patients undergoing CABG are at high risk of experiencing postoperative anxiety, which can negatively affect haemodynamic stability, delay recovery, and impair overall clinical outcomes. Therefore, effective non-pharmacological nursing interventions are needed to manage anxiety during the postoperative period. This study aimed to describe the effectiveness of foot reflexology as a complementary nursing intervention in reducing anxiety in a post-CABG patient using an Evidence-Based Nursing (EBN) approach. Method: This study employed a single-case study design with an Evidence-Based Nursing approach. The subject was a 67-year-old male with a history of hypertension and type 2 diabetes mellitus who underwent three-graft off-pump CABG. Foot reflexology was administered for three consecutive days from postoperative day two to day four, for 30 minutes per foot in each session. Data were collected through comprehensive nursing assessment and analysed descriptively by comparing pre- and post-intervention anxiety levels using the Templer Death Anxiety Scale (DAS), along with changes in vital signs and observed behavioural responses. The patient initially presented with moderate to high anxiety, with a DAS score of 52. Following the intervention, anxiety scores gradually decreased to 45 on the second postoperative day and further to 36 on the fourth postoperative day. Improvements were also observed in vital signs, sleep quality, and overall relaxation, with no adverse effects reported. The application of foot reflexology was proven effective as a complementary nursing intervention in reducing anxiety in post-CABG patients.